Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Efikasi Diri Guru dan Mutu Pembelajaran PAI di Kecamatan Leuwiliang - Suhendi; Ami Primarni; Riyanto (Jurnal Dirosah Islamiyah, 2024)
This study aims to analyze the implementation of the Discovery Learning model and its influence on teacher self-efficacy and the quality of Islamic Religious Education (PAI) learning in Kecamatan Leuwiliang, Bogor Regency. This research uses a qualitative approach with a descriptive method, involving 27 PAI teachers from 9 clusters as key informants. Data were collected through observation, interviews, and documentation studies.The results show that 30% of the teachers have successfully implemented Discovery Learning, demonstrating high self-efficacy and improving learning quality by actively engaging students in the concept discovery process. However, 52% of teachers are aware of the model but do not implement it optimally, leading to varying self-efficacy and learning quality. The remaining 18% of teachers neither know about nor apply the model, continuing with conventional teaching methods, which yield unsatisfactory results.Challenges in implementing Discovery Learning include limited training, inadequate facilities, and insufficient time for lesson preparation. Nevertheless, teachers who received intensive training were able to overcome these obstacles, improving their self-confidence and learning quality. This study concludes that a good understanding and application of Discovery Learning positively impacts PAI teacher self-efficacy and learning quality. Therefore, more efforts are needed to enhance teacher training and mentoring to optimize the implementation of Discovery Learning across elementary schools in Kecamatan Leuwiliang.